A Note on the Determinants of IFRS Policy Choice When Accounting for Non‐controlling Interest and Goodwill. - Aasen, Matilda Hellman; Hellman, Niclas; Hjelström, Tomas; White, Jasmina T. (Abacus, 2026)
This paper provides evidence on the choices made by European firms when measuring non‐controlling interest (NCI) and goodwill. Since 2009, IFRS 3 allows measurement of NCI either at fair value (full goodwill method) or at the proportionate share of net assets (partial goodwill method). IFRS 3 allows this policy choice on a per transaction basis. Our data comprise 188 hand‐collected firm choices in connection with business combinations with remaining NCI, between 2010 and 2016. We use the theoretical framework developed by Stadler and Nobes (2014) explaining differences in firms' choices of overt accounting options by country, industry, and firm‐specific topic factors. Based on univariate and multivariate analyses, we find that transaction‐specific and firm‐specific topic factors influence accounting policy choice, whereas country and industry factors do not. The choice has different effects on financial leverage and operating returns, which inform firm‐level preferences. Regarding choices made at the transaction level, we find acquirers with an intention to buy additional shares from non‐controlling shareholders tend to prefer the full goodwill method. Thus, the choice of accounting method conveys information to users about future additional acquisitions and has implications for standard setters, indicating that offering choices at transaction level may increase the forward‐looking content of financial statements.